CD169+ Macrophages Mediate the Immune Response of Allergic Rhinitis Through the Keap1/Nrf2/HO‐1 Axis - Wenwen Qi; Chengcheng Liu; Lei Shi; Hui Li; Xiaozhi Hou; Hongjie Du; Luqiu Chen; Xiaochen Gao; Xue Cao; Na Guo; Yuhan Dong; Chengzhilin Li; et al. (Advanced Science)
Abstract CD169+ macrophages are a newly defined macrophage subpopulation that can recognize and bind with other cells through related ligands, playing an essential role in antigen presentation and immune tolerance. However, its role in Allergic Rhinitis (AR) is still unclear. To investigate the characteristics of CD169+ macrophages in AR, this work first detects their expression patterns in the nasal mucosa of clinical patients. These results show a significant increase in CD169+ macrophages in the nasal mucosa of patients with AR. Subsequently, this work establishes an animal AR model using CD169 transgenic mice and compared the advantages of the two models. Moreover, this work also demonstrates the effects of CD169 knockout on eosinophils, Th cells, Treg cells, and the migration of dendritic cells (DCs). In addition, this metabolomic data shows that CD169+ macrophages can upregulate alanine production and increase reactive oxygen species (ROS) levels. This process may be mediated through the Keap1/Nrf2/HO‐1 signaling pathway. In addition, this work also finds that SLC38A2 plays an essential role in the process of CD169+ macrophages promoting alanine uptake by DCs. This study confirms that CD169+ macrophages can upregulate their internal alanine production and increase ROS levels through the Keap1/Nrf2/HO‐1 axis, playing an irreplaceable role in AR.